Prostranstvenno-vremennyecharakteristiki techniki pulevoj strel'byu sportsmenov razlicnoj kvalifikacii - Donguzov, Ja. A.; Sidorenko A. I. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2020)
The article discusses the relationship of some technical characteristics of competitive exercises in bullet shooting: the shooting width, accuracy of aiming, the average stability of marks in the ten and the average length of the trajectory measured using the training device «SCATT» and the skill of athletes-shooters. Features of technical characteristics of competitive exercises in bullet shooting for shooters of various qualifications are revealed.